129k views
4 votes
2v^2-12 =-12v
Would really appreciate it loves❤️

User Ugur Eren
by
5.0k points

1 Answer

2 votes

For this case we have the following equation:


2v ^ 2-12 = -12v

Rewriting we have:


2v ^ 2 + 12v-12 = 0

Dividing by 2 to both sides of the equation:


v ^ 2 + 6v-6 = 0

We apply the quadratic formula:


x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}

We have to:


a = 1\\b = 6\\c = -6

Substituting:


x = \frac {-6 \pm \sqrt {6 ^ 2-4 (1) (- 6)}} {2 (1)}\\x = \frac {-6 \pm \sqrt {36 + 24}} {2}\\x = \frac {-6 \pm \sqrt {60}} {2}\\x = \frac {-6 \pm \sqrt {4 * 15}} {2}\\x = \frac {-6 \pm2 \sqrt {15}} {2}

Thus, we have two roots:


x_ {1} = - 3+ \sqrt {15}\\x_ {2} = - 3- \sqrt {15}

ANswer:


x_ {1} = - 3+ \sqrt {15}\\x_ {2} = - 3- \sqrt {15}

User GrayR
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.